2021
DOI: 10.1590/1807-3107bor-2021.vol35.0035
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance pattern of molar-incisor hypomineralization

Abstract: The aim of this study was to investigate the segregation patterns of molar incisor hypomineralization (MIH) in families, given the evidence that its etiology is influenced by genetics. Clinically, MIH may be detected in parents and/or siblings of MIH-affected children. Our study included children with at least one first permanent molar affected by MIH (proband) and their first-degree relatives (parents and siblings). The participants were examined clinically to detect MIH, according to the European Academy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…This high frequency should be explained as the result of corresponding pathogenic mechanisms for both disturbances of tooth structure and development of the primary palate 23 to the multifactorial genetic condition of both MIH and cleft lip and palate that shares the same genetic pathway. 12,13,18,24,25 This result supports the idea that cleft lip and palate were not isolated, but actually a syndrome of alterations of dentition. 18 Considering the cleft type, the low number of patients with cleft palate in the sample is not representative of the frequency of this cleft type in the centre.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This high frequency should be explained as the result of corresponding pathogenic mechanisms for both disturbances of tooth structure and development of the primary palate 23 to the multifactorial genetic condition of both MIH and cleft lip and palate that shares the same genetic pathway. 12,13,18,24,25 This result supports the idea that cleft lip and palate were not isolated, but actually a syndrome of alterations of dentition. 18 Considering the cleft type, the low number of patients with cleft palate in the sample is not representative of the frequency of this cleft type in the centre.…”
Section: Discussionsupporting
confidence: 81%
“…Our study was performed in a cohort of 386 individuals born with cleft lip and/or palate previous to their orthodontic treatment and had not undergone an alveolar bone graft before the photos and clinical examination. This high frequency should be explained as the result of corresponding pathogenic mechanisms for both disturbances of tooth structure and development of the primary palate 23 to the multifactorial genetic condition of both MIH and cleft lip and palate that shares the same genetic pathway 12,13,18,24,25 . This result supports the idea that cleft lip and palate were not isolated, but actually a syndrome of alterations of dentition 18 …”
Section: Discussionsupporting
confidence: 65%
“…Therefore, it is probable that genetic susceptibility and genes might be involved in its phenotype. It has been suggested that the susceptibility to developing MIH is increased by exposure to risk factors such as medication use during amelogenesis [65,66]. Furthermore, although there seems to be an association between genetic polymorphism in enamel formation and MIH, more research is needed for clarification [67].…”
Section: Discussionmentioning
confidence: 99%
“…Etiological studies conducted to date have focused on maternal diseases, stress, medication, alcohol, and cigarette usage in the prenatal period; low birth weight, birth hypoxia, preterm birth, and other defects observed at birth; childhood diseases, exposure to environmental toxins, and long-term and frequent medication usage in the postnatal period [6][7][8][9][10]. It has also been shown that various genetic and epigenetic variants may be involved in the etiology of MIH [6,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%